Enhancing EFL Students’ Speaking Skills through Augmented Reality: A Pre-Experimental Study - Lutfiatul Indana Zulfa; Khoiriyah; Sulistyani (STKIP AL HIKMAH SURABAYA, 2026)
This study investigated the effect of Augmented Reality (AR) on the speaking skills of ninth-grade students at Insan Qur’ani Junior High School. The study addressed the problem of students’ low speaking proficiency, particularly in pronunciation, fluency, grammar, and vocabulary. A quantitative pre-experimental design employing a one-group pre-test and post-test approach was used. The participants consisted of ten ninth-grade students. Speaking performance tests using a rubric adapted from Brown (2004) were used to collect the data. The treatment comprised three meetings employing AR-based learning activities focused on animal descriptions. Data were analyzed by descriptive statistics, validity and reliability tests, normality testing, and paired-sample t-tests. The results showed that the mean score of students’ speaking improved from 61.00 in the pre-test to 81.50 in the post-test. The paired sample t-test found a statistically significant difference between the pre-test and post-test scores (p <.001), indicating that AR had a significantly positive effect on the students’ speaking achievement. Improvements were found on all speaking indicators such as pronunciation, fluency, grammar, and vocabulary. The study found that AR provided a contextualized and interactive learning environment that encourages speaking development and enhances students’ participation and confidence in learning English.